A cryogenic low-background low-noise CMOS preamplifier for HPGe detectors. (1st June 2022) - Hao, J.; He, L.; Deng, Z.
Abstract: A cryogenic low-noise CMOS preamplifier has been successfully developed for HPGe detectors in low-background experiments. Commonly used auxiliary off-chip devices, such as decoupling capacitors and resistors, were removed to control the radioactive emission. The prototype chip was implemented in XFAB 350 nm CMOS process and was fully evaluated. A minimum ENC of 8.9 electrons was obtained at a 12 μs shaping time at 77 K, and the rise time was measured to be 60 ns through a 1-meter-long cable. The performances with and without decoupling capacitors for the power supply and bias voltages were compared, and there was no evident difference between these cases. The performance upon connection to a 0.5 kg point-contact HPGe detector was also measured. A minimum ENC of 15.5 electrons was achieved. The energy spectrum of the 57 Co radiation source was obtained, and the FWHM of the 122 keV energy peak was measured to be 0.6 keV.